Interaction of the nonionic surfactant C12E8 with high molar mass poly(ethylene oxide) studied by dynamic light scattering and fluorescence quenching methods - Feitosa, Eloi [UNESP]; Brown, Wyn; Swanson-Vethamuthu, Martin (American Chemical Society (ACS), 1996)
Dynamic light scattering has been used to investigate ternary aqueous solutions of n-dodecyl octaoxyethylene glycol monoetber (C12E8) with high molar mass poly(ethylene oxide) (PEO). The measurements were made at 20 °C, always below the cloud point temperature (Tc) of the mixed solutions. The relaxation time distributions are bimodal at higher PEO and surfactant concentrations, owing to the preacute of free surfactant micelles, which coexist with the slower component, representing the polymer coil/micellar cluster comptex. As the surfactant concentration is increased, the apparent hydrodynamic radius (RH) of the coil becomes progressively larger. It is suggested that the complex structure consists of clusters of micelles sited within the polymer coil, as previously concluded for the PEO-C12E8-water system. However. C12E8 interacts less strongly than C12E8 with PEO; at low concentrations of surfactant the complex does not contribute significantly to the total scattered intensity. The perturbation of the PEO coil radius with C12E8 is also smaller than that in the C12E8 system. The addition of PEO strongly decreases the clouding temperature of the system, as previously observed for C12E8/PEO mixtures in solution Addition of PEO up to 0.2% to C12E8 (10 wt %) solutions doss not alter the aggregation number (Nagg) of the micelles probably because the surfactant monomers are equally partitioned as bound and unbound micelles. The critical micelle concentration (cmc), obtained from the I1/I3 ratio (a measure of the dependence of the vibronic band intensities on the pyrene probe environment), does not change when PEO is added, suggesting that for neutral polymer/surfactant systems the trends in Nagg and the cmc do not unambiguously reflect the strength of interaction.